2023
DOI: 10.1002/adfm.202300682
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Charge Reversal Nanodrugs for Active Targeting Clearance of Helicobacter Pylori Accompanied by Gut Microbiota Protection

Abstract: Helicobacter pylori (H. pylori) is listed as a definite carcinogen and clinical triple therapy is less satisfactory because H. pylori colonizes beneath the gastric mucous layer and easily forms biofilm. More importantly, the frequent and excessive use of antibiotics causes a disorder of gut microbiota due to the lack of targeting to H. pylori. Here, a kind of protonated charge reversal metal based nanodrugs (MNDs)—ZnO‐Ag‐mercaptoacetamide@chitosan for H. pylori eradication treatment without affecting beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The potential in vivo utility of a multifuntional mucoadhesive system based on chitosan was recently examined in a work by Liu et al. [ 249 ] In this article, the authors indicated that a protonated charged reversal metal‐based nano‐construction namely ZnO‐Ag‐mercaptoacetamide incorporated with chitosan could be a helpful nanosystem to precisely target H. pylori bacteria. The success of this approach could be attributed to four important reasons.…”
Section: Local Delivery Strategies To Combat H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential in vivo utility of a multifuntional mucoadhesive system based on chitosan was recently examined in a work by Liu et al. [ 249 ] In this article, the authors indicated that a protonated charged reversal metal‐based nano‐construction namely ZnO‐Ag‐mercaptoacetamide incorporated with chitosan could be a helpful nanosystem to precisely target H. pylori bacteria. The success of this approach could be attributed to four important reasons.…”
Section: Local Delivery Strategies To Combat H Pylori Infectionmentioning
confidence: 99%
“…Although this excellent study was an example of an advanced approach in the arsenal against mucoadhesive and also mucopenetrative H. pylori bacteria, the nano‐DDS used by Liu et al. [ 249 ] did not address the need to kill H. pylori bacteria which were localized inside the gastric cell cytosol. The importance of mucoinert and cytoadhesive nanostructures in the battle against mucopenetrated and internalized H. pylori is discussed in the following sections.…”
Section: Local Delivery Strategies To Combat H Pylori Infectionmentioning
confidence: 99%
“…Metal-based nanozymes have been favored in fields such as immunoassays, biosensing, and therapy due to their unique electronic properties, good biocompatibility, and chemical stability. Bimetallic nanozymes can be synthesized as random or ordered alloys, core–shell structures, or even Janus-like particles. They have been reported to exhibit excellent enzyme-like activity presumably due to the synergistic or additive effects. The catalytic constant ( K cat ) of bimetallic nanozymes is 2–3 orders of magnitude higher than that of natural horseradish peroxidase (HRP). , Therefore, bimetallic nanozymes have been considered as a promising material for greatly enhancing detection sensitivity .…”
mentioning
confidence: 99%